Characterization of a Novel, Cold-Adapted, and Thermostable Laccase-Like Enzyme With High Tolerance for Organic Solvents and Salt and Potent Dye Decolorization Ability, Derived From a Marine Metagenomic Library - Yang, Qihao; Zhang, Mengle; Zhang, Manman; Wang, Chunqing; Liu, Yanyan; Fan, Xinjiong; Li, He (Frontiers in Microbiology, 2018)
Synthetic dyes are widely used in many industries, but they cause serious environmental problems due to their carcinogenic and mutagenic properties. In contrast to traditional physical and chemical treatments, biodegradation is generally considered an environmental-friendly, efficient, and inexpensive way to eliminate dye contaminants. Here, a novel laccase Lac1326 was cloned from a marine metagenomic library. It showed a maximum activity at 60 C, and it retained more than 40% of its maximal activity at 10 C and more than 50% at 20 C to 70 C. Interestingly, the laccase behaved stably below 50 C, even in commonly used water-miscible organic solvents. The enzyme decolorized all tested dyes with high decolorization efficiency. This thermostable laccase with high decolorization activity and excellent tolerance of organic solvents and salt has remarkable potential for bioremediation of dye wastewater. It is thus proposed as an industrial enzyme.